Wild nights with Emily [videorecording (DVD)]. - Shannon, Molly, 1964-; Seimetz, Amy; Ziegler, Susan (Actor); Gelman, Brett, 1976- (Universal Studios Canadal, 2019)
In the mid-nineteenth century, Emily Dickinson is writing prolifically and enjoying a passionate, romantic relationship with her friend and sister-in-law Susan. While seeking publication of some of her poems, Emily finds herself facing male literary gatekeepers too confused by her genius to take her work seriously. Instead, her work attracts the attention of an ambitious woman editor, who also sees Emily as a convenient cover for her own role in buttoned-up Amherst's most bizarre love triangle.